The perception of employees on whistleblowing effectiveness: evidence from telecommunication public listed companies in Malaysia / Nurzafirah Othman, Raziah Bi Mohamed Sadique and Norhayati Alias - Othman, Nurzafirah; Mohamed Sadique, Raziah Bi; Alias, Norhayati (UiTM Cawangan Negeri Sembilan, 2023)
Most of the time, fraud and misconduct are found unintentionally, and the whistleblower's role is crucial in preventing fraud and corporate misconduct. Whistleblowing exposes an organization's wrongdoing to make it right, not to harm it. Understanding the critical role played by whistleblowers, it is vital to understand the employees' perceptions of the effectiveness of whistleblowing. This study examines employees' perception of whistleblowing effectiveness in telecommunication public listed companies (PLCs) in Malaysia. Previous studies found that organizational support, knowledge of whistleblowing policies, and perceived protections against retaliation affect the perception of employees on whistleblowing globally. This study used a quantitative approach via primary data from close-ended questionnaires. In addition, this study investigated the telecommunication sector in Malaysia. Correlation analysis found a significant moderate positive correlation between the perception of employees on whistleblowing effectiveness in telecommunication public listed companies (PLCs) with organizational support and knowledge of whistleblowing policies; however, there is a significantly low negative correlation with perceived protection against retaliation. Whereas, standard multiple linear regression analysis found that 40.8% variation of the perception of employees on whistleblowing effectiveness in telecommunication public listed companies (PLCs) is explained by the interpretation of three independent variables (organizational support, knowledge of whistleblowing policies, and lastly, perceived protection against retaliation) which means another 59.2% is explained about other things other than three independent variables that have been tested in this study. Given the study's analytical perspectives and realistic recommendations, some drawbacks to this study could be enhanced for future research. Key concerns may be linked to its context, which is restricted to employees employed in telecommunication public listed companies registered under the Main Market of Bursa Malaysia. Future researchers could select employees working in other factors, such as the manufacturing, banking, and automotive industries, when selecting the sample size.